Chiral metallic anticancer drugs: A brief-review - Mukhtar, Sofi Danish; Suhail, Mohammad (European Journal of Chemistry, 2022)
Chiral metallic drugs are becoming the hottest point of discussion in the field of medicinal chemistry. As we know that more than 80% drugs are chiral in nature, and prescribed in the racemic form. The main problem with chiral drugs is the different biological activities of different enantiomers. This is because the human body has a chiral environment, as there is the presence of protein, carbohydrates, enzymes, and other chiral macromolecules. Hence, if a chiral anticancer drug is being prescribed to the patient in the racemic form, it means two or more drugs are being prescribed. Therefore, the chiral separation and analysis of chiral anticancer drugs are important for improving the quality of chiral drug medication. Many metal complexes are used as anticancer drugs, but the conditions become more critical if they have chirality or a chiral moiety, because of which they exist in two or more forms. Because of the presence of chirality or chiral moiety, the complex of metals is termed a chiral metallic complex. Of course, the enantioseparation of the chiral metallic complexes must be done before their prescription. Enantioseparation of the chiral metallic complex will not only provide a pharmaceutically active form to the patient but also reduce the side effects caused by the racemic mixture. Hence, the accessible article reviews the chiral metallic complexes having ruthenium, osmium, palladium, gold, silver, and platinum, etc. as central metal atoms. Besides, the future perspectives regarding the chiral metallic anticancer drugs and the role of their enantioseparation are also discussed.